Efficacy of Otoendoscopy for Residual Cholesteatoma Detection During Microscopic Chronic Ear Surgery - Floor Couvreur; Elke Loos; Christian Desloovere; Nicolas Verhaert (Journal of International Advanced Otology)
BACKGROUND: The aim of this article is to determine the efficacy of otoendoscopy during microscopic cholesteatoma surgery on residual cholesteatoma rates postoperatively.